Religious and Cultural Identity in Political Communication on Social Media in the 2024 Regent Elections in Batubara Regency - Baharuddin; Hasan Sazali; Anang Anas Azhar (Program Pascasarjana IAIN Langsa, 2025)
The 2024 Batubara Regency Regent Election highlighted the use of religious and cultural identity-based political communication in digital spaces, particularly social media. This article aims to analyze the forms, strategies, and impacts of identity political communication constructed by political actors in the contest. Using a critical phenomenological approach and digital content analysis, this study explores how symbols, narratives, and representations of religious and cultural identity are produced, disseminated, and received by the multi-ethnic, predominantly Muslim community of Batubara. The results reveal three main patterns: (1) the use of religious symbols for the moral legitimacy of candidates; (2) the affirmation of local cultural identity as an emotional connection with voters; and (3) the representation of ethnic identity that is sometimes exploited in negative campaigns. Social media, such as Facebook, Instagram, and TikTok, have become primary platforms for the dissemination of identity narratives through hashtags, visual content, and short videos. This study also found a dual impact of identity politics, strengthening the consolidation of support but also causing emotional polarization and social fragmentation. These findings emphasize the importance of identity politics in the Batubara contest, as well as the need to improve political and digital literacy to minimize its negative impacts.